FERTILITY TRANSITION FROM TRADITIONAL TO MODERN MODEL IN MOLDOVA: EXPLORATION IN BASE ON THE GENERATION AND GENDER SURVEY - Grigoraș, Ecaterina; Gagauz, Olga (Economy and Sociology, 2022)
In Moldova, like in other countries of Eastern Europe, after the 1990s, fertility transition from the traditional model to the modern one is occurring. A stable fertility decline was observed up to 2004, while the total fertility rate settled at 1.7-1.8 births per woman in the following years. Although the indicator is higher comparative to other states, the factors determining this level and the likely future trends are essential questions to be asked. We assume some of the sociodemographic characteristics of women, the socioeconomic and cultural context affect the reproductive behavior and determine whether to keep the traditional model or switch to the modern one. The research is conducted to highlight the differences in women's reproductive behavior and the sociodemographic characteristics that influence the number of children born. The research is based on the" Generations and Gender Survey" conducted in Moldova in 2020. A detailed profile of women's reproductive behaviour was presented on the base of four identified clusters, which characterize the fertility transition from the traditional to the modern model. Findings reveal that the traditional model of reproductive behavior with a large family or, at most, with two children is prevalent. Medium and high education, late age at marriage and urban residence of women have a negative effect on the number of children ever born. The study quantifies the heterogeneity of reproductive behavior and has important implications for the scientific perception of current trends and prospective fertility dynamics in Moldova.